Comparison of intravenous lignocaine, dexmedetomidine, and lignocaine-dexmedetomidine infusion for attenuation of pain response to skull pin application in patients of intracranial tumours: A placebo-controlled, double-blinded, randomised comparative study - Swathi Mallikarjuna; Rajnish Arora; Anissa Mirza; Sanjay Agrawal (Indian Journal of Anaesthesia)
Background and Aims: Skull pin application during craniotomy elicits haemodynamic responses that may be detrimental to the patient. This study evaluates and compares the effects of intravenous (IV) lignocaine, dexmedetomidine, and lignocaine-dexmedetomidine on haemodynamic and stress response to skull pins. Methods: This randomised study was conducted on 160 patients aged 18–60 years. Patients for craniotomy with skull pin application were randomly assigned to receive IV lignocaine 2 mg/kg (15 min) followed by 1.5 mg/kg/h (Group L), dexmedetomidine 1 µg/kg (15 min) followed by 0.5 µg/kg/h (Group D), lignocaine 2 mg/kg (15 min) followed by 1.5 mg/kg/h and dexmedetomidine 1 µg/kg (15 min) followed by 0.5 µg/kg/h (Group LD), and normal saline bolus (15 min) followed by 5 mL/h (Group N) for 30 min after skull pin insertion. Haemodynamic variables (heart rate, mean arterial pressure, and bispectral index) and stress response (serum cortisol, prolactin, blood sugar, and neutrophil-lymphocyte ratio (NLR)) were observed at different periods. For group comparisons, a one-way analysis of variance was used for preoperative blood sugar, and the Kruskal-Wallis test was used for heart rate, blood pressure, bispectral index, serum cortisol, serum prolactin, and neutrophil-to-lymphocyte ratio (NLR). Results: Haemodynamic fluctuations were less in groups D and LD. Group LD had decreased levels of serum cortisol (P < 0.001), prolactin (P = 0.315), and NLR (P = 0.002). Blood sugar increased in all groups but was significant in groups N and D (P < 0.001). Conclusion: The dexmedetomidine-lignocaine infusion is associated with few haemodynamic fluctuations and decreased stress response compared to lignocaine or dexmedetomidine alone, hence better in attenuating skull pin response.